2019
DOI: 10.1002/mren.201900033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Investigation of Radical Homopolymerization of 2‐(Methacryloyloxyethyl) Trimethylammonium Chloride in Aqueous Solution

Abstract: The radical homopolymerization kinetics of 2‐(methacryloyloxyethyl) trimethylammonium chloride (TMAEMC) in aqueous solution is investigated across a wide range of initial monomer contents (5–35 wt%), ionic strengths, and pH levels using an in‐situ NMR technique to track monomer consumption over the complete conversion range. Molar mass distributions (MMD) of the final homopolymers are also examined, with additional batch and semi‐batch experiments conducted in a stirred vessel. The rates of monomer conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(62 citation statements)
references
References 45 publications
4
58
0
Order By: Relevance
“…Figure 11b also indicates that the variation in k p /⟨k t ⟩ 0.5 with conversion is relatively small for all initial monomer concentrations, in agreement with the previous study of TMAEMC kinetics by Drawe et al 28 Furthermore, it was found that solution pH, when both lowered (to 2.5) and increased (to 7.5) from the natural pH ∼ 4, had a negligible influence on TMAEMC batch polymerization kinetics. 31 Herein, we compare these TMAEMC results with conversion profiles obtained for MAPTAC using the same in situ NMR technique, also at 50 °C, and covering the same range of initial monomer contents, c M,0 , between 5 and 35 wt %. However, here, the initiator concentration was increased to 0.80 wt % V-50 because of the reduced MAPTAC k p value relative to TMAEMC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 11b also indicates that the variation in k p /⟨k t ⟩ 0.5 with conversion is relatively small for all initial monomer concentrations, in agreement with the previous study of TMAEMC kinetics by Drawe et al 28 Furthermore, it was found that solution pH, when both lowered (to 2.5) and increased (to 7.5) from the natural pH ∼ 4, had a negligible influence on TMAEMC batch polymerization kinetics. 31 Herein, we compare these TMAEMC results with conversion profiles obtained for MAPTAC using the same in situ NMR technique, also at 50 °C, and covering the same range of initial monomer contents, c M,0 , between 5 and 35 wt %. However, here, the initiator concentration was increased to 0.80 wt % V-50 because of the reduced MAPTAC k p value relative to TMAEMC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The k p values show the independence on pH that is expected for these permanently ionized cationic monomers, for which the rate of polymerization has also been shown to be independent of pH. 31 The averaged k p values from these experiments within the pH ranges examined are 2080 ± 120 and 1160 ± 50 L• mol −1 •s −1 for TMAEMC and MAPTAC, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] The method of aqueous solution polymerization is widely used to prepare the polymers due to the advantages of simple technologies, low cost, safe operation, no solvent recovery, and so on. [7][8][9][10] There are few reports on the preparation of PMAPTAC homopolymers by aqueous polymerization method, 11,12 but there is a lack of relevant reports on the homopolymerization kinetics of PMAPTAC. There is only one literature report on the kinetics of research on the copolymerization of acrylamide (AM) and methacrylamidopropyl trimethyl ammonium chloride (MAPTAC).…”
Section: Introductionmentioning
confidence: 99%